Large Language Models for Market Research: A Data-Augmentation Approach - Wang, Mengxin; Zhang, Dennis J.; Zhang, Heng (Marketing Science, 2026)
This paper proposes a statistical data augmentation approach that efficiently integrates LLM-generated data with real data in conjoint analysis.